2023
DOI: 10.1002/cey2.351
|View full text |Cite
|
Sign up to set email alerts
|

Retraction

Abstract: Retraction: Zhang Y, Chen M, Guo P, et al. Magnetic field‐enhanced water splitting enabled by bifunctional molybdenum‐doped nickel sulfide on nickel foam. Carbon Energy. 2023; e351. https://doi.org/10.1002/cey2.351.The above article, published online on 14 March 2023 on Wiley Online Library (wileyonlinelibrary.com), has been retracted by agreement between the authors, journal Editor‐in‐Chief, Shun Wang, and John Wiley & Sons, Inc.The retraction has been agreed as the authors found inconsistencies in the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…with rich reserves and low cost, are considered to be potential candidates for hydrogen production via water splitting. [8][9][10] This is mainly due to the relatively large electronegativity of S (2.5) compared with most other metals, which can further enhance the electrons in the delocalized nickel-based catalysts, Ni-S-based electrocatalysts have been widely studied for their high conductivity and special structural characteristics because they can provide effective electron transfer to promote the migration of electrons from metal cations to S. [11,12] Meantime, Ni-S (Ni 3 S 2 ) is a typical representative of transition metal chalcogenides and exists in nature in the mineral heazlewoodite, which has been intensively investigated as a highly promising electrocatalyst for overall water splitting due to its unique configuration, metallic conductivity, and excellent chemical stability, and an electron acceptor by virtue of the structure feature ─S─S─ units, both of which contribute to the HER and OER simultaneously. [13] However, limited exposure to active sites and unbalanced HER performance severely restrain its electrocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…with rich reserves and low cost, are considered to be potential candidates for hydrogen production via water splitting. [8][9][10] This is mainly due to the relatively large electronegativity of S (2.5) compared with most other metals, which can further enhance the electrons in the delocalized nickel-based catalysts, Ni-S-based electrocatalysts have been widely studied for their high conductivity and special structural characteristics because they can provide effective electron transfer to promote the migration of electrons from metal cations to S. [11,12] Meantime, Ni-S (Ni 3 S 2 ) is a typical representative of transition metal chalcogenides and exists in nature in the mineral heazlewoodite, which has been intensively investigated as a highly promising electrocatalyst for overall water splitting due to its unique configuration, metallic conductivity, and excellent chemical stability, and an electron acceptor by virtue of the structure feature ─S─S─ units, both of which contribute to the HER and OER simultaneously. [13] However, limited exposure to active sites and unbalanced HER performance severely restrain its electrocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 31 created molybdenum-doped nickel sulfide integrated bifunctional electrodes on ferromagnetic nickel foam (Mo–NiS x /NF) by combining in situ spontaneous redox reaction and sulfide reaction. The results show that the overpotential of Mo–NiS x /NF at 50 mA cm −2 (OER) and 10 mA cm −2 (HER) under a magnetic field of 10 000 G is 307 mV and 136 mV, respectively, and it is due to the in situ generated highly active nano-needle-like Mo–NiS x /NF, which forms an integrated catalyst–substrate structure, with the active material and the Ni foam substrate tightly connected with good corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…24 It is reported that the catalyst directly grown on foam nickel (NF) conductor enables the catalyst to obtain a higher catalytic load and larger geometric surface area, NF exhibits excellent intrinsic strength and good conductivity. 14,25,26 Here, we first grow cerium oxide on NF via a hydrothermal method and then obtain NC/NiS-CeO 2 electrocatalyst by sulfurization. The spindle-shaped NC/NiS-CeO 2 catalyst coated with the NC layer shows high catalytic activity for both the OER and HER.…”
Section: ■ Introductionmentioning
confidence: 99%